TGF-β Receptor–dependent Tissue Factor Release and Proteomic Profiling of Extracellular Vesicles from Mechanically Compressed Human Bronchial Epithelial Cells - Mwase, Chimwemwe; Schworer, Stephen A.; Gilmore, Rodney C.; Khan, Faria; Dy, Alane Blythe C.; Haber, Adam L.; Boucher, Richard C.; Randell, Scott H.; Mackman, Nigel; Park, Jin-Ah (American journal of respiratory cell and molecular biology, 2025)
In asthma, tissue factor (TF) concentrations are elevated in the lung. In our previous studies using mechanically compressed human bronchial epithelial (HBE) cells, which are a well-defined model of bronchoconstriction during asthma exacerbations, we detected TF within extracellular vesicles (EVs) released from compressed HBE cells. Here, to better characterize the potential role of this mechanism in asthma, we tested the extent to which the transcriptional regulation of epithelial cell-derived TF varied between donors with and without asthma. Using RNA hybridization, we detected epithelial expression of , the TF protein-encoding gene, in human airways. Next, to determine the role of TGF-β receptor (TGF-βR) in the regulation of TF, we exposed well-differentiated HBE cells to mechanical compression in the presence or absence of a pharmacological inhibitor of TGF-βR. Furthermore, to identify the protein cargo of EVs released from HBE cells, we used tandem mass tag mass spectrometry. Our findings revealed significantly higher expression in the airways of patients with asthma compared with healthy control subjects. However, we observed no differences in expression or TF release between asthmatic and nonasthmatic HBE cells, both at baseline and after compression. Mechanistically, compression-induced expression in HBE cells depended on TGF-βR. Our proteomic analysis identified 22 differentially released proteins in EVs, with higher concentrations in compressed cells compared with controls. Gene Ontology analysis indicates that these proteins are involved in diverse biological processes, highlighting a potential role for epithelial cell-derived EVs during asthma exacerbations.